2017
DOI: 10.1186/s40677-017-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

A method for locating rockfall impacts using signals recorded by a microseismic network

Abstract: Background: Rockfall events are one of the most dangerous phenomena that often cause several damages both to people and facilities. During recent years, the scientific community focused the attention at evaluating the effectiveness of seismological methods in monitoring these phenomena. In this work, we present a quick and practical method to locate the rebounds of some man-induced boulders falls from a landslides crown located in the Northern Apennines (Central Italy). The reconstruction of the trajectories w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
(29 reference statements)
2
14
0
Order By: Relevance
“…1). An 182,000-m 3 unstable rock mass is located in the top area of the quarry (Lotti et al 2015(Lotti et al , 2018Antolini et al 2016;Gracchi et al 2017). It was first observed on May 2003, and it is suggested that the main predisposing factor of the instability was the quarrying activity (Intrieri et al 2012).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…1). An 182,000-m 3 unstable rock mass is located in the top area of the quarry (Lotti et al 2015(Lotti et al , 2018Antolini et al 2016;Gracchi et al 2017). It was first observed on May 2003, and it is suggested that the main predisposing factor of the instability was the quarrying activity (Intrieri et al 2012).…”
Section: Study Areamentioning
confidence: 99%
“…Moreover, the early warning framework can also be implemented with alternative or complementary localization methods, such as those based on arrival times (Gracchi et al 2017), beam-forming (Lacroix and Helmstetter 2011), and amplitude source location (Pérez-Guillén et al 2019). The examples of signals and frequencies of these events are shown in Fig.…”
Section: Spatial Estimationmentioning
confidence: 99%
“…More recently, to overcome these limitations, rock slope stability characterization and monitoring has been carried out using passive seismic techniques (see also the discussion session), implemented initially in open-mine monitoring [98]. These techniques, in fact, could help in (i) understanding the seismic responses of rock to slope deformation (e.g., the release of stored elastic energy under particular conditions) [135,138], (ii) detecting and locating microearthquakes generated by fracturing within unstable rock masses (major effort is required for classifying seismic signals and extracting those related to landslides [86,99,129]), and (iii) identifying remote events that could otherwise go unnoticed for weeks or months. Therefore, these methods are applied to avalanches [26,84,101,126], rock topplings [107,111,117,134], rockslides [55, 96-99, 103, 116, 126, 127, 130], and rock falls or cliff failures [86, 88, 89, 91, 93-95, 100, 104-106, 112-115, 118, 120, 121, 126, 128, 131, 133].…”
Section: "Rock"mentioning
confidence: 99%
“…Along the roads produced from excavated hills, rockfall is definitely to be one of the most potential threats that could happen, but not all segments of the roads have the same levels of hazard. Rockfall impacts were identified by Gracchi et al (2017) as a combination of several functions, one of which is geomechanics conditions. In this study, geomechanics conditions of an area will be analyzed as a significant factor that affecting the hazard level of rockfall.…”
Section: Introductionmentioning
confidence: 99%